2018
DOI: 10.1186/s12957-018-1373-y
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node cancer of the mediastinum with a putative necrotic primary lesion in the lung: a case report

Abstract: BackgroundAlthough mediastinal lymph node cancer is presumed to originate in the lung, the primary site is usually unidentified, so the pathological course remains unclear. We recently encountered a case of mediastinal lymph node cancer having a putative primary lesion remaining in the lung as a necrotic focus.Case presentationThe patient was a 56-year-old man who visited our department because computed tomography screening had revealed a nodular shadow in the lingular segment. However, on positron emission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, the patient exhibited no respiratory symptoms throughout the disease course. Failure to detect the primary site may be related to not only the small size, but also the involvement of immunologic mechanisms leading to the spontaneous regression of the primary lesion [ 15 ]. Therefore, clinicians must perform a comprehensive and systematic screening to rule out tumors if a patient with polymyositis presents with symptoms unrelated to polymyositis in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the patient exhibited no respiratory symptoms throughout the disease course. Failure to detect the primary site may be related to not only the small size, but also the involvement of immunologic mechanisms leading to the spontaneous regression of the primary lesion [ 15 ]. Therefore, clinicians must perform a comprehensive and systematic screening to rule out tumors if a patient with polymyositis presents with symptoms unrelated to polymyositis in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 40% of reported cancers of the hilar, mediastinal, and cervical lymph nodes, the site of primary malignancy was estimated to be the lung [28]. Taking into account the pathway of regional lymph flow in the lung, occult microcarcinoma can be considered to be present in the lung in cases of mediastinal lymph node CUP [29,30]. However, it is not rare for cancer of a distant organ, such as colorectal cancer or breast cancer, to metastasize to mediastinal lymph nodes [31,32,33,34,35], so identification of the primary focus has important implications for treatment selection.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, oligometastases have been treated by surgical resection, because surgical resection is anecdotally believed to yield survival benefits (7,8). However, recently, SRS and stereotactic ablative body radiotherapy (SABR) have often replaced surgery for the treatment of oligometastasis (20,21).…”
Section: Editorial Commentarymentioning
confidence: 99%
“…In general, conditions with 1-3 or 1-5 metastatic lesions are defined as an oligometastatic cancer (5,6). Based on this concept, many oligometastatic diseases are now treated by local therapies with curative intent worldwide (7,8). Andrews et al demonstrated in 2004 that adding stereotactic radiosurgery (SRS) to whole-brain radiotherapy boosted median overall survival (OS) from 4.9 to 6.5 months in patients with a single unresected brain metastasis (9).…”
mentioning
confidence: 99%